Population and lifestyle trend changes in China: implications for environmental quality - Apergis, N.; Li, Jun (Routledge, 2016)
© 2016. Demographic changes have considerable impacts on a country’s long-term growth trajectory through the savings, consumption and labour market channels. Population changes, including ageing, migration and urbanization, as well as lifestyle shifts may affect growth for fast-growing countries like China. Rural population migrating to cities consumes more energy services and produces larger emissions since urban lifestyles are generally more energy- and carbon-intensive. Household structures also keep changing across the majority of Chinese cities. Migration and urbanization together drive China’s energy consumption, CO2 emissions upwards and environmental quality downwards if the current trend continues over time. It is, thus, necessary for China to draw useful lessons from experiences in other countries by reconciling population development and environmental changes. This study provides insights into the challenge of environmental sustainability, resulting jointly from population and lifestyle changes in China over the period 1978–2012. The empirical analysis generates empirical findings documenting that population changes and consumption behavioural changes contributed significantly to increased carbon emissions over the last three decades. The modelling results are highly relevant for policymakers who seek to adopt new policies to mitigate lifestyle change-driven environmental challenges that China has to cope with in the foreseeable future.